Addition of Avocado Peel Extract (Persea americana) in CEP Diluent on Spermatozoa Quality of Simmental Bull at 4-5°C - Utami, Istiqomah Indah; Ducha, Nur (LenteraBio : Berkala Ilmiah Biologi, 2023)
Storage of semen at low temperatures decrease in the quality of spermatozoa, one of which is due to Reactive Oxygen Species (ROS), therefore a diluent with antioxidants is needed to protect spermatozoa. Antioxidants can be sourced from natural materials, for example Avocado Fruit Peel Extract (EKBA). This study was aimed to determine the effect of adding avocado peel extract, as well as concentration in maintaining the sperm quality of Simmental Bull at 4-5°C. The research design used was a completely randomized design with 5 treatments giving 0% EKBA concentration; 1%; 2%; 3%; and 4% with 4 repetitions. Motility of individual spermatozoa observations was carried out with a 400x magnification under a light microscope. Viability of spermatozoa was observed using eosin-negrosin staining method and observed with a 400x magnification under a microscope. The membrane integrity of the spermatozoa cell observation with Hypo-Osmotic Swelling Test (HOST) fluid and observed under microscope. The data were analyzed using one-way ANOVA test and continued with Duncan test. The result showed that addition of EKBA significantly affected sperm quality of Simmental Bull (p<0.05). The treatment of 3% EKBA showed a motility result of 46.25 ± 1.85%, viability of 77.82% ± 0.90%, and membrane integrity of 78.76 ± 1.30% which was optimal compared to other treatments. Based on the results study, it can be concluded that the addition of 3% EKBA in Caudal Epididymal Plasma (CEP) diluent had highest value with optimal concentration in maintaining the quality of spermatozoa in storage at 4-5°C for 4 days.